(untitled) (Journal of Informatics Education and Research, 2025)
From the standpoint of IT governance, this study explores the relationship between financial technology (FinTech) usage and sustainability performance in Indian commercial banks. Utilizing snowball sampling and nonprobability convenience methods, data were gathered from 210 banking professionals. The study employs structural equation modeling to analyze how IT governance moderates the interplay between FinTech adoption and sustainability-related initiatives. Findings reveal a strong interconnection between FinTech, IT governance, and sustainability, emphasizing the need for an integrated approach to sustainable banking. Financial institutions can enhance long-term growth and economic sustainability by incorporating FinTech, ESG principles, and IT governance into their strategies. The research highlights that IT governance significantly influences banks’ strategic engagement in sustainable activities, facilitates FinTech development, and positively impacts sustainability performance. Beyond enhancing financial and environmental outcomes, IT governance fosters technological adoption, promoting economic sustainability. Financial institutions that proactively integrate IT governance with sustainability-focused innovations are positioned to achieve both environmental and financial benefits. Furthermore, the findings provide valuable insights for policymakers and banking executives, emphasizing the importance of balancing sustainability efforts with technological advancements while addressing potential trade-offs in economic and environmental performance.